66.2k views
2 votes
Solve for k.


9(3-2x)=2(10-8x)

User Alfredo EM
by
5.3k points

1 Answer

7 votes

Answer:

Explanation:

9(3−2x)=2(10−8x)

Step 1: Simplify both sides of the equation.

9(3−2x)=2(10−8x)

(9)(3)+(9)(−2x)=(2)(10)+(2)(−8x)(Distribute)

27+−18x=20+−16x

−18x+27=−16x+20

Step 2: Add 16x to both sides.

−18x+27+16x=−16x+20+16x

−2x+27=20

Step 3: Subtract 27 from both sides.

−2x+27−27=20−27

−2x=−7

Step 4: Divide both sides by -2.

−2x −2 = −7 /−2

x= 7/ 2

Answer:

x= 7/ 2

User Paulus Potter
by
5.5k points